Effect of multi‐walled carbon nanotubes on rheological behavior and electrical conductivity of poly(ethylene‐co‐vinyl acetate)/acrylonitrile‐butadiene rubber/multi‐walled carbon nanotubes nanocomposites. Issue 12 (22nd September 2022) - Razavi‐Nouri, Mohammad; Salavati, Masoud
Abstract: In this work, the effect of multi‐walled carbon nanotubes (MWCNTs) on electrical conductivity and rheological behavior of poly(ethylene‐co‐vinyl acetate) (EVA)/acrylonitrile‐butadiene rubber (NBR) blends containing 0 to 7 wt% MWCNTs are investigated. The theoretical calculations according to the interfacial free energy of the components revealed that the nanofillers had a tendency to locate in NBR domains. However, the rheological, electrical, and morphological studies indicated that the majority of the MWCNTs remained in the EVA phase. Shear creep measurements of the molten materials showed that the creep stability improved steadily with the increase in MWCNTs content. The creep behaviors of the materials, except EVA, were analogous to the Burgers model prediction and all four parameters of the model increased in value with the increase in the nanofillers content in comparison with those of the unfilled blend. The rheological studies indicated that the damping factor (tanδ) for the materials containing small amounts of the nanofillers reached a maximum and subsequently decreased with rising temperature. However, for the materials having 1 wt% MWCNTs and higher, the tanδ values were smaller at the highest temperature (200°C) than those of the lowest temperature (100°C) investigated in this work. The electrical percolation threshold was also found to take place at about 2.80 wt% MWCNTs loading. Abstract :